Sodium thiosulfate protects human aortic smooth muscle cells from osteoblastic transdifferentiation via high‐level phosphate. Issue 11 (5th September 2013) - Zhong, Hui; Liu, Fang; Dai, Xiaoyu; Zhou, Li; Fu, Ping
Abstract: Vascular calcification is recognized as a common complication in some patients, such as chronic renal failure. The purpose of this study was to investigate the role of sodium thiosulfate (STS) for the transdifferentiation of human aortic vascular smooth muscle cells into osteoblast‐like cells induced by high‐level phosphate. All human aortic vascular smooth muscle cells were divided into STS group 1 (treatment with STS) and STS group 2 (culture in a medium containing a high level of phosphate). STS group 1 included a normal group, a high‐level phosphate group, and other subgroups based on treatment with different concentrations of STS. Cells of STS group 2 were cultured in a medium containing a high level of phosphate for 72 hours, and then divided into a high‐phosphate control group and other subgroups based on treatment with different concentrations of STS. The mRNA and protein expressions of bone morphogenetic protein‐2 (BMP‐2), core binding factor α‐1 (Cbfα‐1), and matrix Gla protein (MGP) were detected. Meanwhile, calcium concentration and alkaline phosphatase (ALP) activation were measured. In STS group 1, the mRNA levels of BMP‐2 and Cbfα‐1 were elevated significantly in the high‐level phosphate group compared with the normal group ( p < 0.05). However, both gene expressions were attenuated in the STS‐treated groups (vs. normal group, p < 0.05). MGP mRNA levels were reduced in the high‐level phosphate group (vs. normal group, p < 0.05). In the STS‐treated groups, mRNA expression of MGP was elevated compared to the high‐level phosphate group ( p < 0.05). In STS group 2, expression of MGP was enhanced significantly (vs. high‐phosphate control group, p < 0.05) with both BMP‐2 and Cbfα‐1 reducing in the STS‐treated groups (vs. high‐phosphate‐control group, p < 0.05). STS attenuates calcium concentration and ALP activation. It can reverse osteoblast differentiation of vascular smooth muscle cells and modulate the expressions of calcification‐related factors.